A randomised controlled trial of a couples‐based sexuality intervention for men with localised prostate cancer and their female partners. Issue 7 (8th December 2014) - Chambers, Suzanne K.; Occhipinti, Stefano; Schover, Leslie; Nielsen, Lisa; Zajdlewicz, Leah; Clutton, Samantha; Halford, Kim; Gardiner, Robert A.; Dunn, Jeff
Abstract Objective The diagnosis and treatment of prostate cancer is followed by substantive sexual morbidity. The optimal approach for intervening remains unclear. Methods/design A three‐arm randomised control trial was undertaken with 189 heterosexual couples where the man had been diagnosed with prostate cancer and treated surgically. The efficacy of peer‐delivered telephone support versus nurse‐delivered telephone counselling versus usual care in improving both men's and women's sexual adjustment was investigated. Assessments were undertaken at baseline (pre‐test) with follow‐up at 3, 6 and 12 months. Results At 12 months, men in the peer (p = 0.016) and nurse intervention (p = 0.008) were more likely to use medical treatments for erectile dysfunction (ED) than men in the usual care arm. Men in the nurse intervention more frequently used oral medication for ED than men in usual care (p = 0.002). No significant effects were found for sexual function, sexuality needs, sexual self‐confidence, masculine self‐esteem, marital satisfaction or intimacy. Conclusion Although peer and nurse couples‐based interventions can increase use of medical treatments for ED, this may not translate into better sexual or relationship outcomes. More research is needed into the optimal timing of interventions to improve sexual outcomes for men with prostate cancer and to identify the subpopulations that will benefit from them. Copyright © 2014 John Wiley & Sons, Ltd.